Analisis Hubungan Gaya Kepemimpinan Dan Talent Management Terhadap Kinerja Karyawan PT. Marsyavin Jaya - Maria Kaok (Musamus University, Merauke Papua Indonesia., 2019)
Human Resources (HR) assets and capital in the company and organization the purpose of this study is to find out and analyze the Style of Leadership and Talent Management of Employee Performance at PT. Marsyavin Jaya Merauke Regency. This research is a quantitative research using survey, interview, and questionnaire methods. The data analysis technique uses multiple linear regression analysis, with the results of the X1 variable test the t-test leadership style is 5.720 and the talent management X2 variable is 4.236 with the f-test 432.278 which explains that the variables X1 and X2 have a positive effect on the Y variable. multiple linear variable X1 leadership style 0.365 and X2 talent management variable 0.240. Simultaneous tests with a value of 0.973 and the rest are influenced by other variables not examined.